CORALS FROM THE TOURNAISIAN-VISÉAN BOUNDARY LAYERS OF THE DONETS BASIN - OHAR, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Boundary Tournaisian-Viséan layers in the Donets basin (Centralny quarry) are studied. Sharp changes in their lithology and coral assemblages are found. They are caused by a global eustatic event.